The Hidden Aromaticity in Borazine - Pino-Rios, R (Royal Society of Chemistry, 2022)
The aromaticity of borazine (B3N3H6), also known as the inorganic benzene, is a controversial issue since this compound has several characteristics that could qualify it as an aromatic compound. However, recent studies using magnetic criteria indicate that this compound should be considered as a non-aromatic system. This assignment is mainly due to diatropic currents in the nitrogen atoms without observation of ring currents. The present work shows by means of the magnetic criteria that borazine has a ring current hidden by the local contributions of degenerate orbitals π1 and π2. Additionally, the study of borazine s first triplet state antiaromaticity using the magnetic and energetic criteria by means of isomerization stabilization energies (ISEs) together with Baird s and Hückel s rules suggests that borazine is best described as an (weakly) aromatic system. © 2022 Royal Society of Chemistry. All rights reserved.